Assessing Technology Integration in Teaching and Learning within Open Distance Education - Masengo Ilunga; Bolanle Ikotun; Lusiwe Maduna (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Technology for teaching and learning in engineering is assessed in this study on specific variables related to graduate attributes, assessment, technology use and student performance in open distance education. The results revealed the consistency of the variable measurements. Technology was shown to be very satisfactory for all variables, which displayed generally some degree of acceptable correlation. Hence, the variables under investigation were consistently interrelated and correlated when considering technology as common element to the variables. The use of software or other technological tools were also shown to be satisfactory in the context of school of Engineering, University of South Africa.